PENGARUH PENGGUNAAN SARUNG TANGAN DENGAN BANTALAN DAN TAPPING TERHADAP PENURUNAN NYERI CARPAL TUNNEL SYNDROME - B L, Abdurahman Berbudi; Setiawan, Heru; Achwan, Achwan; Kurniawan, Ganesa Puput Dinda (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
Carpal tunnel syndrome is a disorder that occurs in the wrist where inside the wrist there is a carpal tunnel through which the median nerve passes, as a result of excessive movement or pressure on the carpal tunnel which causes irritation of the median nerve. The aim of this study is to determine the effect of using gloves with pads and taps to reduce carpal tunnel syndrome pain, this research method used a pre and post experimental design, as many as 50 people were given gloves with pads and taps, the research subject was someone who worked more than 3 hours riding a motorbike in 1 day, in When driving, the wrist gets pressure when slowing down the vehicle and when passing through winding roads. The research subjects used gloves for 10 working days in two weeks, and used tapping for 2 weeks with a duration of 1 day on for 8 hours, 1 day off. The results of this study were 31 men and 19 women with an average age of 32.2 years and a pain average of 4.54 before and after 1.84 on the vas scale. In the statistical tests carried out, the value p=0.0001 was obtained where p< 0.05 so it can be concluded that the use of gloves and taps can reduce pain in cases of carpal tunnel syndrome.